Women's Cultural Empowerment as a Public Libraries Gateway towards Sustainable Development - menassel, mourad (Journal of Social Sciences and Humanities, 2020)
The study aims to spot the different roles of the public libraries in promoting sustainable development and achieving its development strategy vision 2030, and realizing its goals through the cultural empowerment of girls through a close knowledge of the set of services provided and the programmed activities in addition to the various programs and cultural events aimed at the girls in The annexes of the main public library of tebessa (El Aouinet, Skanska, Hammamet) in order to respond to their multiple needs, develop their capacities, develop their skills and culturally empower them as a main base for achieving sustainable development within the framework of the international vision 2030. For this purpose, the study adopted a descriptive approach based on the analysis and concluded with a number of results. The most important of these are:The libraries focus on the females as much as the males and equally interested to ensure the female's right to information and knowledge and to enable them to have equal rights in cultural activities, programs and events , the libraries also provide the essential elements for a suitable environment for developing girls' abilities and developing their skills by ensuring that girls have the right to cultural development and to ensure their equal access to information and knowledge.